Endoscopic diagnosis and treatment of esophageal verrucous squamous cell cancer. Issue 5 (15th October 2012) - Sweetser, S.; Jacobs, N. L.; Wong Kee Song, L. M.
Summary Verrucous squamous cell cancer (VSCC) of the esophagus is a variant of squamous cell carcinoma. This rare entity has been described in only a handful of case reports in the literature. We sought to evaluate the endoscopic features, treatment, and outcomes related to esophageal VSCC. The medical records of all patients with esophageal VSCC seen at our institution from January 1995 to December 2010 were reviewed retrospectively. A total of 11 patients (6 men; mean age 66 years [range 57–75 years]) were identified, with a mean follow up of 4 years (range 0.5–10 years) available in nine patients after diagnosis. About half the patients smoked or consumed alcohol on a regular basis. The median time interval from onset of symptoms to diagnosis of esophageal VSCC was 2.5 years (range 1–20 years), with dysphagia being present in all patients. The majority of tumors (8 of 11) exhibited a white, warty, plaque‐like appearance with superimposed Candida at endoscopy, which led solely to a diagnosis of Candida esophagitis on initial presentation. The disease was either extensive (n = 5) throughout the esophagus or localized (n = 6) often by tumor nodules or projections, with the lower third of the esophagus being most commonly involved. Initial pinch biopsies were nondiagnostic in eight (73%) of the patients. Six patients underwent esophagectomy; neoadjuvant chemoradiation therapy was provided in two. In patients treated solely with surgery and who had a preoperative endoscopic ultrasound, the latter tended to overestimate staging of the lesion relative to surgical pathologic staging. Two patients were deemed to be poor operative candidates and received only chemoradiation treatment. One patient with a T2N0 tumor by endoscopic ultrasound staging was managed symptomatically with intermittent endoscopic dilation because of significant comorbidities that precluded surgery and oncologic therapy. There has been no evidence for residual or recurrent neoplastic disease in the eight patients who received treatment with surgery and/or chemoradiation therapy. Five of six patients who underwent surgery have required intermittent endoscopic dilation of anastomotic strictures during follow up. One of the two patients who received only chemoradiation therapy has required periodic endoscopic dilation for radiation‐induced esophageal stricture. Two of the nine (22%) patients have died of causes unrelated to VSCC or its treatment at last follow up. In conclusion, a high index of suspicion for esophageal VSCC should be raised by the presence of long‐standing symptoms coupled with white, warty esophageal lesions seen on endoscopic evaluation. Candida overgrowth can be expected to confound the diagnosis. Despite the long duration of symptoms, surgical resection typically shows relatively low‐grade tumors, consistent with the rare propensity of this variant of esophageal squamous cell carcinoma to metastasize.